Formation of MeV energy ion beams with high current density for materials micro-irradiation - Romanenko, A.V.; Ponomarev, A.G.; Miroshnichenko, V.I. (Вопросы атомной науки и техники, 2013)
A numerical analysis has been performed for the optimum configuration of a probe-forming system based on magnetic quadrupole lens multiplets in a nuclear scanning microprobe intended for irradiations of micron-size areas. The current densities expressed via the reduced collimated acceptance were calculated as function of the spot dimensions for working distances ranging from 4 to 24 cm. Consideration is being given to the advantages of the doublet of magnetic quadrupole lenses as a probe-forming system. Проведено теоретичний чисельний аналіз оптимальної конфігурації зондоформуючої системи на базі мультиплетів магнітних квадрупольних лінз у ядерному скануючому мікрозонді для задач опромінення мікроскопічних областей матеріалів. Знайденo залежності густини струму, вираженні через приведений колімований аксептанс, від розмірів плями на мішені для робочих відстаней у діапазоні 4…24 см. Показано перевагу використання в якості зондоформуючої системи дублету магнітних квадрупольних лінз. Проведен теоретический численный анализ оптимальной конфигурации зондоформирующей системы на базе мультиплетов магнитных квадрупольных линз в ядерном сканирующем микрозонде для задач облучения микроскопических областей материалов. Найдены зависимости плотности тока, выраженные через приведенный коллимированный аксептанс, от размеров пятна на мишени для рабочих расстояний в диапазоне 4…24 см. Показано преимущество использования в качестве зондоформирующей системы дублета магнитных квадрупольных линз.